Simulation‐based design of a microfabricated pneumatic electrospray nebulizer. Issue 3 (14th November 2014) - Jarvas, Gabor; Grym, Jakub; Foret, Frantisek; Guttman, Andras; Foret, Franta; Kutter, Jörg P.
<x xml:space="preserve">Abstract</x> A microfabricated pneumatic electrospray nebulizer has been developed and evaluated using computer simulations and experimental measurements of the MS signals. The microdevice under development is designed for electrospray MS interfacing without the need to fabricate an electrospray needle and can be used as a disposable or an integral part of a reusable system. The design of the chip layout was supported by computational fluid dynamics simulations. The tested microdevices were fabricated in glass using conventional photolithography, followed by wet chemical etching and thermal bonding. The performance of the microfabricated nebulizer was evaluated by means of TOF‐MS with a peptide mixture. It was demonstrated that the nebulizer, operating at supersonic speed of the nebulizing gas, produced very stable nanospray (900 nL/min) as documented by less than 0.1% (SE) fluctuation in total mass spectrometric signal intensity.